Drivers of Sustainable Rural Growth and Poverty Reduction in Central America : Nicaragua Case Study, Volume 1. Executive Summary and Main Text - World Bank (2013)
This regional study encompasses three Central American countries: Nicaragua, Guatemala, and Honduras. The focus of this report is Nicaragua. The objective of the study is to understand how broad-based economic growth can be stimulated, and sustained in rural Central America. The study identifies "drivers" of sustainable rural growth and poverty reduction, where drivers are defined as the assets and combinations of assets needed by different types of households in different geographical areas to take advantage of economic opportunities, and improve their well-being over time. The study examines the relative contributions of these assets, and identifies the combinations of productive, social, and location-specific assets that matter most to raise incomes, and take advantage of prospects for poverty-reducing growth. The study's focus on assets is appropriate given historically stark inequalities in the distribution of productive assets among households in the region. Such inequalities are likely to constrain how the poor share in the benefits of growth, even under appropriate policy regimes. In Nicaragua, economic potential has a strong spatial pattern, with high potential areas close to the main cities. But to generate substantial gains in poverty reduction and broad-based growth, complementarities between productive, social, and location-specific assets must be addressed. The report thus recommends the move from geographically untargeted investments in single assets, to a more integrated and geographically based approach of asset enhancement with proper complementarities. And, if the development objective is to reach the largest number of poor, invest in a variety of social and productive household assets, in higher potential areas with the highest rural poverty densities. However, remote areas such as the Atlantic, need specialized analyses and differentiated strategies and investments. The report highlights the need for more strategic convergence in linking the investment, and impacts of sectoral projects backed by the Bank, and other donors in the diverse geographical regions of the country.